(untitled) (CIPEEX, 2023)
This study aimed to define the procedures for the management of two native Cerrado species: Caryocar villosum Pers. and Caryocar brasiliense Cambess, located in rural areas of the state of Goiás. Analyses were conducted on the relationships between the main morphometric indices of the crown and growth in diameter and height. For this, the diameter at breast height, total height, insertion height, and crown diameter of 206 trees were measured. In the analysis of crown parameters, Caryocar brasiliense demonstrated superiority in diameter and area; indicating that this species requires a larger vital space and greater initial spacing for the development of its ecological characteristics.